Damage to Coral Reef Ecosystem Studies By Coastal Community Activity in District Sikakap Mentawai District - alex sandra, Dio; Hermon, MP, Dr. Dedi; Syarief, M.Si, Azhari (STKIP PGRI Sumbar, 2014)
ABSTRACT Â Dio Alex Sandra (09030244) : Damage to Coral Reef Ecosystem Studies By Coastal Community Activity in District Sikakap Mentawai District .This study aims to gain an overview of Damage Coral Reef Studies By Coastal Community Activity in District Sikakakap Mentawai District : 1 ) The threat of damage , 2 ) Management Procedures , 3 ) Community perception .This research is descriptive qualitative and quantitative approach , respondents were 35 people . testing the validity of the data in the study used data collection techniques , and tringulasi .Based on the results of the data analysis and discussion of matters concluded as follows : 1 ) The threat of damage to coral reefs in the District Sikakap Mentawai District in general by comparing community activities such as making building materials that had been filled from marine mining and retrieval rock . 2 ) so far COREMAP program in coral reef management efforts that have been done almost meet all the objectives of this acceleration . 3 ) The people of the District Sikakap have known that coral reefs is not an inanimate object , but different species and community knowledge regarding the function of Ecology is also quite deep coral reefs .